Management of Rotator Cuff Injury with Physiotherapy in Pre- and Post-surgery: An Overview - Kudshiya Khan; Guisia Khan; Aafreen; Asad Jamal Ansari; Ebadurrahman; Abdur Raheem Khan (International Journal of Orthopedic Nursing and Practices, 2023)
The likelihood of rotator cuff tears increases with age, with total width tears occurring in roughly 25% of people in their 60s and an extra 50% of people in their 80s. Despite the fact that surgery is considered an active therapy, repeated rips at the inset place are common, particularly during progressive tears, which are common in the elderly population. Physical therapy and exercise therapy are currently receiving more attention as a way to treat partial and complete rotator cuff strains by treating weakness and effective arrears. Affected role selection for physical treatment and exercise has been advised by recent teachings to have best result, an enhancement in purpose, and achievement in avoiding surgery. Yet, once an elderly patient continues to be active and has very efficient needs, surgical activity becomes increasingly reciprocal. Studies in ageing populations had produced positive therapeutic and clinical outcomes after invasive restoration. Decompressing is a less harmful and intrusive opportunity that has remained useful to deliver temporary pain reprieve, although permanent interventions may become less effective with time. The goal of this clinical commentary is to describe the function of physical therapy in the pre- and post-surgical care of rotator cuff injury.
Keywords: Rehabilitation; physiotherapy; rotator cuff repairs; rotator cuff tears; surgical management